2022
DOI: 10.1073/pnas.2115871119
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of an ancient branching program to suppress carpel development in maize flowers

Abstract: Carpels in maize undergo programmed cell death in half of the flowers initiated in ears and in all flowers in tassels. The HD-ZIP I transcription factor gene GRASSY TILLERS1 (GT1) is one of only a few genes known to regulate this process. To identify additional regulators of carpel suppression, we performed a gt1 enhancer screen and found a genetic interaction between gt1 and ramosa3 (ra3). RA3 is a classic inflorescence meristem determinacy gene that encodes a trehalose-6-phosphate (T6P) phosphatase (TPP). Di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 143 publications
(177 reference statements)
1
24
0
Order By: Relevance
“…3). However, upon backcrossing to B73, the strength of this phenotype decreased to that described previously for gt1 (Klein et al, 2022;Whipple et al, 2011). This suggests that the silky tassel phenotypes of double mutants are subject to the regulation of a modifier in the initial background that is not present in the B73 background (Suppl Fig 3).…”
Section: Gt1 and Vrl1 Exhibit Joint Roles In Growth Repression In Ear...mentioning
confidence: 59%
See 2 more Smart Citations
“…3). However, upon backcrossing to B73, the strength of this phenotype decreased to that described previously for gt1 (Klein et al, 2022;Whipple et al, 2011). This suggests that the silky tassel phenotypes of double mutants are subject to the regulation of a modifier in the initial background that is not present in the B73 background (Suppl Fig 3).…”
Section: Gt1 and Vrl1 Exhibit Joint Roles In Growth Repression In Ear...mentioning
confidence: 59%
“…Floral organs are also derepressed in gt1; ra3 double mutant tassels (Klein et al, 2022). We compared the gene expression changes accompanying the derepression of pistils in tassel inflorescences in gt1; ra3 maize plants (Klein et al, 2022) with the gene expression changes observed here. Only three genes were shared between the wildtype versus gt1; vrl1 DE genes and the pre-pistil suppression stage wild-type versus gt1; ra3 DE genes (Klein et al, 2022).…”
Section: Single Meristem Transcriptome Sequencing Shows That Gt1 and ...mentioning
confidence: 93%
See 1 more Smart Citation
“…its function aside from the catalysis of Tre6P dephosphorylation 53 . Subsequent study also demonstrated “moonlighting” function of RA3 in carpel suppression 54 . Rather regulatory than a catalytic function was also proposed for TPP7 in Oryza sativa , due to its low activity in vitro and no apparent effect on Tre6P content in knockout mutants of TPP7 55 .…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, RA3 and GT1 appear to regulate genes implicated in PCD, including homologs of the Arabidopsis (Arabidopsis thaliana) NAC transcription factors (TFs) KIRA1 and ANAC087 [13][14][15].…”
Section: Pcd During Sex Determinationmentioning
confidence: 99%